2017
DOI: 10.33546/bnj.158
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Massage Therapy Alone and in Combination With Green Coconut Water Therapy on B-Endorphin Level in Teenage Girls With Dysmenorrhea

Abstract: Background: Dysmenorrhea is pain during menstruation in lower abdomen, and is not due to other diseases. Effleurage massage and consuming green coconut water are considered able to reduce menstrual pain. However, little is known about the effect of the combination between the two interventions.Objective: To compare the effectiveness of effleurage massage and in combination with green coconut water on pain, anxiety, and ß-endorphin level in teenage girls with menstrual pain (dysmenorrhea).Design: A quasy experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
3
0
4
Order By: Relevance
“…Massage effleurage during the pandemic that is carried out regularly by the elderly will be able to reduce and prevent complications due to hypertension. According to previous research from Harris & Richards (2010) combined isotonic and isometric resistance exercise effectively modifies endothelial function in hypertensive patients and increases endothelium vasodilation so as to prevent arteriosclerosis (Ulya et al, 2017) and can improve the quality of life of the elderly (Putra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Massage effleurage during the pandemic that is carried out regularly by the elderly will be able to reduce and prevent complications due to hypertension. According to previous research from Harris & Richards (2010) combined isotonic and isometric resistance exercise effectively modifies endothelial function in hypertensive patients and increases endothelium vasodilation so as to prevent arteriosclerosis (Ulya et al, 2017) and can improve the quality of life of the elderly (Putra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Level in Teenage Girls with Dysmenorrhea" adanya pengaruh yang signifikan terhadap penurunan tingkat kecemasan dan nyeri, serta meningkatkan β-kadar endorfin pada remaja saat nyeri haid. Hal ini dikarenakan pijat effleurage bertujuan untuk meningkatkan sirkulasi darah, memberi tekanan, menghangatkan otot perut serta meningkatkan kesehatan fisik dan relaksasi mental (Ulya et al, 2017).…”
Section: Hal Ini Juga Sejalan Dengan Penelitian Tentang "Comparisson ...unclassified
“…Interviews were conducted with the Student Affairs Section and some female students, which revealed that 40 of them had experienced primary dysmenorrhea. The most prevalent way of managing dysmenorrhea was through the consumption of anti-pain medication or by resting [8].…”
Section: Introductionmentioning
confidence: 99%